“Black box operation” in carbon reduction: Based on empirical evidence of carbon transfer by subsidiaries of Chinese enterprises - Li, Jianti; Luo, Xin; Feng, Dawei (Frontiers in Environmental Science, 2023)
Avoiding the transfer of "carbon" and encouraging the digestion of "carbon" are essential to promote the green and low-carbon transformation of China's economy. In accordance with the standpoint of off-site subsidiaries, this paper examines the transfer of "carbon" from high-carbon enterprises using the data of A-share listed companies from 2009 to 2018 using a DID approach and the 2013 China carbon emissions trading pilot as a quasi-natural experiment. As demonstrated by the reach findings: (1) Part of the effect of corporate "carbon reduction" is achieved by shifting high-carbon sectors. (2) As demonstrated in mechanism analysis, when high-carbon companies face the dual cost pressure of R&D expenditure and purchasing carbon trading rights, they will establish subsidiaries to avoid the parent company's pressure to lessen emissions. As revealed in heterogeneity analysis. (3) companies with stronger R&D capabilities and higher success rates are more willing to respond to the impact of carbon trading policies with technological upgrades. Companies with weaker R&D capabilities and higher failure rates are more likely to choose to transfer "carbon" to avoid the "dual cost" of R&D failures. (4) Owing to the constraint of the migration threshold, the trajectory of "carbon" transfer is primarily domestic interregional transfer supplemented by cross-country transfer. (5) Larger enterprises emitting more "carbon", are not only more likely to pay more "carbon" reduction costs in the face of carbon policy shocks, are but also more likely to shift "carbon". This study not only provides a new perspective to explain the "carbon" transfer phenomenon in China, but also provides crucial policy implications for further strengthening environmental governance as well as regional joint prevention and control in China.